Atmospheric memories: Affect and minor politics at the ten-year anniversary of the London bombings - Angharad Closs Stephens (Emotion, Space and Society, 2017)
This paper addresses how the ten-year anniversary of the London bombings was made present through political affects and atmospheres on 7 July 2015. Although the anniversary of a terrorist event forms an opportune moment for invoking the nation as united in feeling, we are interested in how people attune to political atmospheres of memory and trauma in multiple ways, which do not always cohere to sovereign narratives about unity and certainty. By focusing on these events through an attentiveness to the atmospheric and affective, we examine how these events were recalled, memorialised, felt and sensed in the small-scale ceremonies taking place across London on that morning, by way of a multi-authored sensory auto-ethnography. As such, we are led towards various moments of encounter, which involve ‘minor gestures’ (Manning, 2016), and imply ways of responding to acts of terror that rub against the unifying forces of the state. In contrast to the ‘rolling maelstroms of affect’ (Thrift 2004: 57) pursued by the state and media following a terrorist attack, this project is attentive to multiple, uncertain and ambivalent encounters. These matter because they suggest other ways of being political and of responding to both terrorist and state-led violence.